“Diseño de un sistema de gestión de calidad basado en la Normativa ISO 9001:2015 para la empresa Rectificadora Cotopaxi”. - Pilco Chango, Jonathan Xavier (2024)
The objective of this project is the design of a Quality Management System based on the ISO 9001:2015 standard for the company Rectificadora Cotopaxi, this company carries out rectification processes for internal combustion engines and wishes to standardize its service generation processes. At the same time, it seeks continuous improvement of its technical service, aimed at customer satisfaction. The characterization of this process delimited the activities carried out within the organization considering work areas, machinery, tools and supplies involved in the rectification. In addition, a checklist established by the ISO 9001:2015 standard was applied, which made it possible to demonstrate that the organization maintains a percentage of 11.85% of system implementation, this is because the organization is not governed by any system. quality management, operates based on experience or empirical knowledge, in informality and on the application and documentation of the requirements set out in the standard. The quality management manual developed establishes a structured and systematic framework that will allow quality to be managed and continuously improved at all stages of the engine rectification process. The ISO 9001:2015 standard provides a set of internationally recognized requirements and guidelines to establish, implement, maintain, and improve an effective QMS. The design represents a significant opportunity to improve quality, efficiency and competitiveness in the processes of the aforementioned company.